Body Mass Index: A Risk Factor for Retinopathy in Type 2 Diabetic Patients - Kaštelan, Snježana; Tomić, Martina; Gverović Antunica, Antonela; Ljubić, Spomenka; Salopek Rabatić, Jasminka; Karabatić, Mirela (Mediators of Inflammation, 2013)
The aim of the study was to investigate whether body mass index (BMI) independently or in correlation with other risk factors is associated with diabetic retinopathy (DR) progression. The study included 545 patients with type 2 diabetes. According to DR status, they were divided into three groups: group 1 (no retinopathy; n=296), group 2 (mild/moderate nonproliferative DR; n=118), and group 3 (severe/very severe NPDR or proliferative DR; n=131). Patients without DR were younger than those with signs of retinopathy at time of diabetes onset whilst diabetes duration was longer in groups with severe NPDR and PDR. DR progression was correlated with diabetes duration, BMI, HbA1c, hypertension, and cholesterol. Statistical analyses showed that the progression of retinopathy increased significantly with higher BMI (gr. 1: 26.50 ± 2.70, gr. 2: 28.11 ± 3.00, gr. 3: 28.69 ± 2.50; P<0.01). We observed a significant deterioration of HbA1c and a significant increase in cholesterol and hypertension with an increase in BMI. Correlation between BMI and triglycerides was not significant. Thus, BMI in correlation with HbA1c cholesterol and hypertension appears to be associated with the progression of DR in type 2 diabetes and may serve as a predictive factor for the development of this important cause of visual loss in developed countries.